2012
DOI: 10.1007/s00018-012-1018-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the regulation of iron metabolism during the prenatal and early postnatal periods

Abstract: Molecular iron metabolism and its regulation are least well understood in the fetal and early postnatal periods of mammalian ontogenic development. The scope of this review is to summarize recent progress in uncovering the molecular mechanisms of fetal iron homeostasis, introduce the molecules involved in iron transfer across the placenta, and briefly explain the role of iron transporters in the absorption of this microelement during early postnatal life. These issues are discussed and parallels are drawn with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 133 publications
(193 reference statements)
2
53
0
9
Order By: Relevance
“…Preliminary data of this work were disclosed earlier 43 and were recently discussed. 44 While this manuscript was in preparation, erythropoietic abnormalities of IRP1 2/2 mice were also reported by others. 45,46 Ghosh et al 45 further showed that IRP1 2/2 mice develop pulmonary hypertension, an additional pathology shared by Chuvash polycythemia patients 47 and the respective mouse model.…”
Section: 39supporting
confidence: 60%
“…Preliminary data of this work were disclosed earlier 43 and were recently discussed. 44 While this manuscript was in preparation, erythropoietic abnormalities of IRP1 2/2 mice were also reported by others. 45,46 Ghosh et al 45 further showed that IRP1 2/2 mice develop pulmonary hypertension, an additional pathology shared by Chuvash polycythemia patients 47 and the respective mouse model.…”
Section: 39supporting
confidence: 60%
“…It is increased with higher erythropoiesis or decreased in conditions of iron overload (Lipinski et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal IDA is particularly frequent and severe in pigs, regardless of the breed and the system of piglet rearing [3], [4]. Iron scarcity in piglets is the result of interplay of several distinct risk factors such as low level of iron stores, increased iron requirements, limited external supply and the immaturity of molecular mechanisms of iron absorption [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…For decades pigs have been selected for large litter size, high birth weight and fast growth, which resulted in greater body blood volume, red blood cells (RBC) count, and in consequence, in increased iron demands. Both hepatic iron reserves and the sow’s milk are therefore nowadays not sufficient to meet iron requirements in suckling piglets [3], [4], [7]. Moreover, the molecular machinery responsible for iron absorption in newborn piglets is not fully developed, and this may explain a reduced responsiveness of these animals to oral iron therapy [8], [9].…”
Section: Introductionmentioning
confidence: 99%